Etudes sur le terrain et en laboratoire des causes de la mortalite ovine dans les hauts plateaux ethiopiens en 1986-1987 - Njau, B.C.; Kasali, O.B.; Scholtens, R.G.; Degefa, M. (1988)
Reports the major specific causes of sheep mortality in the Debre Berhan area between July 1986 and June 1987. Includes data on seasonal crude death rates, causes of mortality, frequency and age at death.